2021
DOI: 10.1590/1413-812320212612.14942021
|View full text |Cite
|
Sign up to set email alerts
|

Violências relacionadas ao trabalho e variáveis associadas em profissionais de enfermagem que atuam em oncologia

Abstract: Resumo A violência ocupacional é um agravo ao qual os profissionais de saúde estão cotidianamente expostos. O objetivo deste artigo é identificar a prevalência de violência no trabalho (verbal/física) e as variáveis relacionadas em profissionais de enfermagem atuantes em oncologia. Estudo transversal, em que a agressão física ou verbal foi avaliada por meio do autorrelato. Analisou-se a relação entre as variáveis sociodemográficas, psicoemocionais e relacionadas ao trabalho violência (verbal/física) por meio d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
4
4
0
5
Order By: Relevance
“…After adjusting the multiple model, which allowed to control the effect of possible confounding variables, the occurrence of physical and/or verbal violence was associated with increasing age and symptoms of anxiety (moderate/severe), the latter identified through the application of inventories which, in this and other studies 11,15,16 , showed high internal consistency. The association with age had already been reported in previous studies 10, 14 . It is possible that older individuals, because they have more professional experience, are better able to identify situations of violence, especially less noticeable types, such as verbal violence and bullying.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…After adjusting the multiple model, which allowed to control the effect of possible confounding variables, the occurrence of physical and/or verbal violence was associated with increasing age and symptoms of anxiety (moderate/severe), the latter identified through the application of inventories which, in this and other studies 11,15,16 , showed high internal consistency. The association with age had already been reported in previous studies 10, 14 . It is possible that older individuals, because they have more professional experience, are better able to identify situations of violence, especially less noticeable types, such as verbal violence and bullying.…”
Section: Discussionsupporting
confidence: 81%
“…Review studies indicate prevalences ranging from 7% to 85%, depending on the country, professional category, work sector, type of violence, among other factors 19, 23 . In a national study, for example, a prevalence of 62% was found among nursing professionals working in oncology 14 . In China 24 and Nigeria 25 , rates in multiprofessional samples were 77% and 88% respectively; and in Bosnia-Herzegovina 26 , it was 90% among primary care physicians and nurses.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…', podendo haver resposta dicotômica (sim ou não). A agressão física foi considerada como o uso da força que resulta em dano físico ou psicológico; e a agressão verbal, como o uso de palavras em atitudes ofensivas com o objetivo de humilhar, caluniar ou envergonhar um indivíduo ou um grupo 4, 14 .…”
Section: Methodsunclassified
“…Saúde mental dos enfermeiros em tempos de pandemia: reflexões sobre a qualidade do sono nos ambientes laborais As alterações psicoemocionais dos profissionais de enfermagem podem ser atribuídas ainda à violência relacionada ao trabalho. A maior exposição aos pacientes e acompanhantes proporciona uma maior vulnerabilidade a atos agressivos, o que gera um maior desgaste emocional (SANTOS et al, 2021).…”
Section: Temática 1 -Correlação Da Qualidade Do Sono E Adoecimento Em...unclassified